Sustainability Analysis of Oil Palm Business (Elaeis Guineensis) In District Of Sebatik, Nunukan Regency, North Kalimantan, Indonesia - Etty Wahyuni; Khaerunnisa Khaerunnisa; Marlina Marlina (Agribusiness Journal, 2022)
Palm oil is one of the most strategic commodities because it is exports and has a high selling value so that it can improve the economy regions and reduce poverty. Smallholder oil palm plantations as part of the palm oil agribusiness supply chain which is slowly being required to implement aspects continuity. This study aims to analyze the sustainability status of farming palm oil based on index assessment using the Rapfish method through Multidimensional Scaling (MDS) approach. Multidimensional analysis of MDS used are ecological, economic, social, technological and institutional dimensions as the aspects studied in this research. This research was conducted in Sebatik District, North Kalimantan, Indonesia. The data used are primary and secondary data. Primary data obtained from interviews with farmers while secondary data was obtained from the statistical center, plantation service and supporting literature in this research. Respondents in this study were farmers who were selected through quota sampling have certain criteria totaling 50 respondents. The results of analysis for multidimensional index of oil palm sustainability in Sebatik District is 51.01 including in the moderately sustainable category. While the results of the analysis of the sustainability index for five dimensions are 76.57 (ecological), 50.63 (economic), 24.03 (social), 37.12 (technology), 63.49 (institutional). The entirety of each entry dimension includes in the category of “sufficiently sustainable” except for the social and technological dimensions with category "less sustainable". Sustainability of oil palm farming in each dimension have different sustainability indices so that a different policy is needed to evaluate the sustainability of oil palm farming in Sebatik District, North Kalimantan, Indonesia.